HUBUNGAN AKTIVITAS FISIK DENGAN KEJADIAN DEMENSIA PADA LANSIA DI PANTI SOSIAL YAYASAN SRIKANDI BANDAR SURABAYA LAMPUNG TENGAH TAHUN 2021 - Topan Pamungkas Ariestya; Arena Lestari; Gunawan Irianto (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2022)
The elderly are at risk of developing dementia. With increasing age, the risk of dementia will increase, this is exacerbated by the physical activity of the elderly. The Srikandi Bandar Surabaya Foundation facilitates nursing homes for the elderly to continue physical activity in their old age. However, dementia cases were still 26% in 2019. This study aims to determine the relationship between physical activity and the incidence of dementia in the elderly at the Srikandi Foundation Social Institution, Bandar Surabaya, Central Lampung in 2021. This research is a quantitative analytic observational through a cross sectional approach. The population in this study were all the elderly at the Srikandi Bandar Surabaya Foundation in 2021. The sample of this study amounted to 35 respondents. The sampling technique in this study used a total sampling technique. This research activity was carried out at the Srikandi Bandar Surabaya Foundation in August 2021. The analysis was carried out with the Chi Square statistical test.The results in this study obtained the most good physical activity (45.7%), most of the respondents did not experience dementia (60.0%). there is a relationship between physical activity and the incidence of dementia in the elderly at the Srikandi Bandar Surabaya Foundation social home, Central Lampung in 2021 (P value = 0.027; CC = 0.414). It is recommended for the elderly to do physical activity to prevent dementia with support from caregivers.